Karakteristik Kompresibilitas dan Kuat Geser pada Tanah Lempung Berdasarkan Uji CPT, SPT dan Laboratorium di Cikarang: Compressibility and Shear Strength Characteristics of Clay Based on CPT, SPT and Laboratory Tests in Cikarang - Bambang Suharyadi; Aswin Lim; Rinda Karlinasari (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2024)
The Jakarta-Cikampek Elevated toll road was built to add to the existing toll road section. In this project, the field investigation tests carried out are the Cone Penetrartion test (CPT) and the Standard Penetration Test (N-SPT). Many studies have been conducted to obtain the compressibility value (cc) and shear strength value (su) of clay because each clay in a region has different compressibility characteristics and shear strength values. This study aims to determine the compressibility characteristics and shear strength of clay in the Cikarang area by using field investigation data in the form of CPT test of 10 points and N-SPT test of 12 points and laboratory data used from N-SPT drill points of 21 tube samples. CPT and N-SPT data are grouped based on the closest distance, the test area is dominated by Sandy clay and the linear regression equation obtained from both data relationships is qc = 0.51N with an upper limit equation qc = 1.2N and for the lower limit qc = 0.2N. From the results of the analysis for the shear strength value of the soil obtained from the relationship of the shear strength value of the soil to the N-SPT of Su = 8N-SPT, and for the level of compressibility at the location in Cikarang has a high level of compressibility with the relationship of compressibility to the pore number (eo) obtained equation Cc = 0.40eo and with the level of activity of relatively inactive clay soil.